Endodontic Management of a Mandibular First Molar with Four Canals in a Distal Root by Using Cone-Beam Computed Tomography: a Case Report - Hani Baziar; Farzaneh Daneshvar; Abbas Mohammadi; Hamid Jafarzadeh (eJournal of Oral Maxillofacial Research)
Background: Aberrations in the root canal anatomy are clinically challenging for clinicians. Mandibular first molars usually have 2 roots and 3 or 4 canals, but various combinations may exist. A distal root with three canals is rare and its incidence in literature is about 0.2 - 3%. As a diagnostic tool, cone-beam computed tomography (CBCT) may be a better choice for diagnosis of extra roots or canals comparing to conventional radiography.